Answer:
Now
Using
ym = m x λ x L/d
therefore for each of first Max we have m =1
And laser 1 had
y = (d/20) x (6.0m)/d
y = 6.0m /20 = 0.3
Then laser 2 will be
y = 6.0m/15 = 0.4
y ( laser1 ) < y ( laser2 )
So the first maxima of laser 1 will be closer to the Central maxima
So
(0.4m -0 .3 m) = 0.1m
( C)
Now for laser 1 we say
y= 26.0 m / 20 = 0.6 m
Laser 2
We have
ym=(m+1/2) x λ x L/d
So
Because there is no central minimum the first minimum is at m = 0
We can way 3rd minimum is at m = 2
So
y = (2.5) x 6.0 / 15 = 1m
So
Δy= 1m - 0.6m = 0.4 m